Control of cytokinin and auxin homeostasis in cyanobacteria and algae - Žižková, Eva; Kubeš, Martin; Dobrev, Petre I; Přibyl, Pavel; Šimura, Jan; Zahajská, Lenka; Záveská Drábková, Lenka; Novák, Ondřej; Motyka, Václav (Annals of botany, 2017)
BACKGROUND AND AIMS: The metabolism of cytokinins (CKs) and auxins in vascular plants is relatively well understood, but data concerning their metabolic pathways in non-vascular plants are still rather rare. With the aim of filling this gap, 20 representatives of taxonomically major lineages of cyanobacteria and algae from Cyanophyceae, Xanthophyceae, Eustigmatophyceae, Porphyridiophyceae, Chlorophyceae, Ulvophyceae, Trebouxiophyceae, Zygnematophyceae and Klebsormidiophyceae were analysed for endogenous profiles of CKs and auxins and some of them were used for studies of the metabolic fate of exogenously applied radiolabelled CK, [(3)H]trans-zeatin (transZ) and auxin ([(3)H]indole-3-acetic acid (IAA)), and the dynamics of endogenous CK and auxin pools during algal growth and cell division. METHODS: Quantification of phytohormone levels was performed by high-performance or ultrahigh-performance liquid chromatography-electrospray tandem mass spectrometry (HPLC-MS/MS, UHPLC-MS/MS). The dynamics of exogenously applied [(3)H]transZ and [(3)H]IAA in cell cultures were monitored by HPLC with on-line radioactivity detection. KEY RESULTS: The comprehensive screen of selected cyanobacteria and algae for endogenous CKs revealed a predominance of bioactive and phosphate CK forms while O- and N-glucosides evidently did not contribute greatly to the total CK pool. The abundance of cis-zeatin-type CKs and occurrence of CK 2-methylthio derivatives pointed to the tRNA pathway as a substantial source of CKs. The importance of the tRNA biosynthetic pathway was proved by the detection of tRNA-bound CKs during the course of Scenedesmus obliquus growth. Among auxins, free IAA and its oxidation catabolite 2-oxindole-3-acetic acid represented the prevailing endogenous forms. After treatment with [(3)H]IAA, IAA-aspartate and indole-3-acetyl-1-glucosyl ester were detected as major auxin metabolites. Moreover, different dynamics of endogenous CKs and auxin profiles during S. obliquus culture clearly demonstrated diverse roles of both phytohormones in algal growth and cell division. CONCLUSIONS: Our data suggest the existence and functioning of a complex network of metabolic pathways and activity control of CKs and auxins in cyanobacteria and algae that apparently differ from those in vascular plants.
Keywords: homeostáza; Cyanobacteria; sinice; Tandem Mass Spectrometry; vysokoúčinná kapalinová chromatografie; Indoleacetic Acids; Chlorophyta; Homeostasis; cytokininy; Cytokinins; Phylogeny; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; kyseliny indoloctové; Streptophyta; regulátory růstu rostlin; fylogeneze; Spectrometry, Mass, Electrospray Ionization; Plant Growth Regulators